Optimization of In vivo Imaging Provides a First Look at Mouse Model of Non-Alcoholic Fatty Liver Disease (NAFLD) Using Intravital Microscopy - Davis, Rachelle P.; Surewaard, Bas G. J.; Turk, Madison; Carestia, Agostina; Lee, Woo-Yong; Petri, Björn; Urbanski, Stefan J.; Coffin, Carla S.; Jenne, Craig N. (Frontiers in Immunology, 2020)
Non-alcoholic fatty liver disease is a spectrum of liver pathology ranging from simple steatosis to steatohepatitis and can progress to diseases associated with poor outcomes including cirrhosis and hepatocellular carcinoma (HCC). NAFLD research has typically focused on the pathophysiology associated with lipid metabolism, using traditional measures such as histology and serum transaminase assessment; these methods have provided key information regarding NAFLD progression. Although valuable, these techniques are limited in providing further insight into the mechanistic details of inflammation associated with NAFLD. Intravital microscopy (IVM) is an advanced tool that allows for real-time visualization of cellular behaviour and interaction in a living animal. Extensive IVM imaging has been conducted in liver, but, in the context of NAFLD, this technique has been regularly avoided due to significant tissue autofluorescence, a phenomenon that is exacerbated with steatosis. Here, we demonstrate that, using multiple imaging platforms and optimization techniques to minimize autofluorescence, IVM in fatty liver is possible. Successful fatty liver intravital imaging provides details on cell trafficking, recruitment, function and behavior in addition to information about blood flow and vessel dynamics, information which was previously difficult to obtain. As more than 30% of the global population is overweight/obese, there is a significant proportion of the population at risk for NAFLD and complications due to NAFLD (liver decompensation, cirrhosis, HCC). IVM has the potential to elucidate the poorly understood mechanisms surrounding liver inflammation and NAFLD progression and possesses the potential to identify key processes that may be targeted for future therapeutic interventions in NAFLD patients.